Late initiation of antenatal care and associated factors among pregnant women attending antenatal clinic at Hiwot Fana Comprehensive Specialized Hospital, Eastern Ethiopia: a cross-sectional study - Bayisa Dibaba; Miressa Bekena; Tariku Dingeta; Eshetu Refisa; Habtamu Bekele; Shambel Nigussie; Eyobel Amentie (Frontiers Media S.A., 2024)
BackgroundLate initiation of antenatal care (ANC) is a major public health concern. If women initiate ANC late, they do not get adequate care, reducing the chances of early detection of pregnancy-related complications. However, there is a lack of data related to the initiation of antenatal care in the study area.ObjectivesTo assess the prevalence of late initiation of antenatal care and identify associated factors among pregnant women attending antenatal care at Hiwot Fana Comprehensive Specialized Hospital, Eastern Ethiopia.MethodsAn institutional-based cross-sectional study design was conducted among 454 pregnant women. All eligible participants during the study period were included. Data were collected via face-to-face interviews, were entered into Epi Data version 4.3, and analyzed using SPSS version 22 software. The results are presented using texts and tables. Logistic regression with the 95% confidence interval (CI) was used to identify factors associated with the late initiation of antenatal care. Statistical significance was declared at P < 0.05.ResultsThe prevalence of late-initiation antenatal care in this study was 59.5% (95% CI 54.6-63.4). Age range of 30-34 years [adjusted odds ratio (AOR) 2.7, 95% CI 1.69-13.1] and age ≥35 years (AOR 4.2, 95% CI 1.92-9.84), rural residency (AOR 2.92, 95% CI 1.59-5.39), unplanned pregnancy (AOR 2.3, 95% CI 1.35-8.11), inability to make the decision to start ANC (AOR 2.14, 95% CI 1.18-3.89), multigravidity (AOR 1.9, 95% CI 1.13-12.4), wrong perception on the time of antenatal care initiation (AOR 5.8, 95% CI 3.71-9.34), lack of previous ANC experience (AOR 2.01, 95% CI 1.14-5.81), and more than 10 km distance from the hospital (AOR 1.36, 95% CI 0.62-2.95) were associated with late initiation antenatal care in this study.ConclusionMore than half of the study participants were initiated into ANC after the 12th week of gestation. Moreover, rural residence, unplanned pregnancy, age ≥30 years, lack of previous antenatal care, inability to make decisions, and wrong perception on the time of initiation of ANC were found to be associated with late initiation of ANC. Educating women and involving partners and family members in discussions about ANC were recommended to build a supportive environment for pregnant mothers.